2001
DOI: 10.1093/oxfordjournals.molbev.a003748
|View full text |Cite
|
Sign up to set email alerts
|

The DIRS1 Group of Retrotransposons

Abstract: Only three retrotransposons of the DIRS1 group have previously been described: DIRS1 from the slime mold Dictyostelium discoideum, PAT from the nematode Panagrellus redivivus, and Prt1 from the zygomycetous fungus Phycomyces blakesleeanus. Analyses of the reverse transcriptase sequences encoded by these elements suggest that they are related to the long terminal repeat (LTR) retroelements, such as the Ty3/gypsy retrotransposons and the vertebrate retroviruses. The DIRS1-group elements, however, have several un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 27 publications
6
93
0
Order By: Relevance
“…For instance, for many cryptons we found that the extreme termini contain a short sequence (4-6 bp) which is repeated at either end, and this same sequence appears in the related empty sites. A similar situation was found for DIRS1-like elements (Goodwin & Poulter, 2001a) and also occurs with at least some elements from the Ngaro1 group (T. J. D. Goodwin, unpublished data). For the DIRS1 elements, we interpreted these findings as suggesting that the extrachromosomal transposition intermediates of these elements integrate into the host genome by recombination between a short sequence at the circular junction of the element's termini and an identical sequence in the target site.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…For instance, for many cryptons we found that the extreme termini contain a short sequence (4-6 bp) which is repeated at either end, and this same sequence appears in the related empty sites. A similar situation was found for DIRS1-like elements (Goodwin & Poulter, 2001a) and also occurs with at least some elements from the Ngaro1 group (T. J. D. Goodwin, unpublished data). For the DIRS1 elements, we interpreted these findings as suggesting that the extrachromosomal transposition intermediates of these elements integrate into the host genome by recombination between a short sequence at the circular junction of the element's termini and an identical sequence in the target site.…”
Section: Discussionsupporting
confidence: 74%
“…Percentages of bootstrap support, from 1000 replicates, are indicated for branches receiving >40 % support. The sources of many sequences are given in a previous report (Goodwin & Poulter, 2001a). Others are listed in Methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms of these two types of retoelements are summarized briefly here and in Figure 2. In addition, two smaller retrotransposon families, the DIRS1 (Goodwin and Poulter 2001) and BEL (Malik et al 2000) groups, appear to be distinct, but are much less widely distributed, and thus, will not be discussed further here.…”
Section: Two Types Of Retrotransposons That Mobilize By Distinct Mechmentioning
confidence: 99%